2020
DOI: 10.1177/1129729820936411
|View full text |Cite
|
Sign up to set email alerts
|

In defense of the use of peripherally inserted central catheters in pediatric patients

Abstract: Central venous access devices have revolutioned the care of children affected by malignancies, facilitating management of complex and prolonged infusive therapies, reducing pain and discomfort related to repeated blood samples and indiscriminate venipunctures, thus reducing also psychological stress of both patients and families. In this respect, peripherally inserted central catheters have been disseminated for use, even in pediatric oncology patients, for their many advantages: easy and non-invasive placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…A number of studies (10,32,35) have shown that the occurrence of CRT is unavoidable, but the incidence of thrombosis can be reduced by taking active preventive measures, such as strengthening limb movement training after catheterization, strengthening the training of catheterization operators, selecting the appropriate catheter (30,36), standardizing the CVC flushing and sealing operation, preventing the use of anticoagulants in highrisk patients (37), and adopting interstitial limb pneumatic therapy after catheterization. The specific methods and frequencies of physical training such as limb activities, the specific requirements of CVC tube flushing and sealing operation, and the specific implementation methods of various interventions need to be further refined.…”
Section: Discussion On Measures To Prevent Crt In Children With Cvcsmentioning
confidence: 99%
“…A number of studies (10,32,35) have shown that the occurrence of CRT is unavoidable, but the incidence of thrombosis can be reduced by taking active preventive measures, such as strengthening limb movement training after catheterization, strengthening the training of catheterization operators, selecting the appropriate catheter (30,36), standardizing the CVC flushing and sealing operation, preventing the use of anticoagulants in highrisk patients (37), and adopting interstitial limb pneumatic therapy after catheterization. The specific methods and frequencies of physical training such as limb activities, the specific requirements of CVC tube flushing and sealing operation, and the specific implementation methods of various interventions need to be further refined.…”
Section: Discussion On Measures To Prevent Crt In Children With Cvcsmentioning
confidence: 99%
“…This is mainly due to the introduction of an information system in this intervention model, that is, through the establishment of electronic medical records, QQ group, microphone group, and the digitization of each patient's information through such as a platform, the nursing staff can obtain the patient's electronic medical record at any time and record the specific diagnosis and treatment of the patient at each diagnosis and treatment stage, PICC, etc. [ 8 , 9 ]. At the same time, the PICC health knowledge will be pushed in the group regularly, so that the patients and their families have a deeper understanding of the relevant health knowledge and improve the patients' mastery of each health knowledge, so that the patients can know the necessity and importance of the relevant intervention measures so that they can more actively carry out PICC nursing and effectively improve their compliance in the diagnosis and treatment process [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that included in the bundle of care for central venous access devices it is strongly recommended to employ a subcutaneous securement device in order to reduce catheter related complications. [10][11][12] Long-term antibiotic therapy is traditionally administered through a PICC line, but when veins are of poor caliber, or the decision is made to place the line in a central vein, ultrasound should be used to thoroughly assessment the deep veins of the arm, supra/infra-clavicular region, and the groin. Literature supports the safety of central venous access when ultrasound guidance is incorporated in the insertion.…”
Section: Discussionmentioning
confidence: 99%